Developing and validating lean manufacturing constructs: an SEM approach - Nawanir, Gusman; Lim, Kong Teong; Siti Norezam, Othman; Adeleke, A. Q. (Emerald, 2018)
1) Purpose – To provide valid and reliable constructs for lean manufacturing (LM) for assessing its implementation level in order to target areas of improvement. 2) Design/methodology/approach – Based on an extensive review on LM literature and content validity assessment from practitioners and academicians, nine LM constructs were identified. Measurement items for each construct were developed to become a complete questionnaire. The questionnaire booklets were distributed to large and discrete manufacturing companies in Indonesia. Out of 1,000 survey questionnaires sent, 236 usable responses were returned giving response rate of 23.60%. Subsequently, an empirical assessment on the constructs was done by using structural equation modeling approach. 3) Findings – The study identified the valid and reliable LM constructs, consisting of nine LM constructs and 64 measurement items. The study found that all the constructs are complementary and mutually supportive with each other. Indeed, it suggests the holistic implementation of all the LM practices. 4) Research limitations/implications – Owing the time and resource constraint, this study only involved large and discrete process manufacturing industries in Indonesia. Hence, the generalization of the result is slightly limited. More studies in several different contexts are required. 5) Practical implications – This study provided a valuable tool for researchers for gaining deeper understanding regarding the LM and its implementation. For practitioners, it is useful to evaluate the degree of LM employment in their companies, to target area of improvement, as well as to take possible actions in attempting to enhance the organizational performance. More importantly, practitioners should adopt all the LM practices in a holistic manner. 6) Originality/value – This study represents the first attempt to develop LM constructs for evaluating the LM implementation in Indonesia.